The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1073/pnas.1100224108
|View full text |Cite
|
Sign up to set email alerts
|

Structural context for mobilization of a human tRNA synthetase from its cytoplasmic complex

Abstract: Human lysyl-tRNA synthetase is bound to the multi-tRNA synthetase complex (MSC) that maintains and regulates the aminoacylation and nuclear functions of LysRS. The p38 scaffold protein binds LysRS to the MSC and, only with the appropriate cue, mobilizes LysRS for redirection to the nucleus to interact with the microphthalmia associated transcription factor (MITF). In recent work, an ðα 2 Þ 2 LysRS tetramer crystallized to yield a high-resolution structure and raised the question of how LysRS is arranged (dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 56 publications
(77 reference statements)
1
32
0
Order By: Relevance
“…The phosphomimetic S207D LysRS mutant is unable to bind p38/AIMP2 or any component of the MSC (16), which would increase the pool of free LysRS. Additionally, S207D LysRS has been shown to trigger a more "open" conformation, resulting in abolition of aminoacylation but not tRNA binding capacity in vitro (16,43). Our data are consistent with these previous findings and also show that S207D LysRS still binds tRNA Lys3 as well as WT LysRS.…”
Section: Discussionsupporting
confidence: 82%
“…The phosphomimetic S207D LysRS mutant is unable to bind p38/AIMP2 or any component of the MSC (16), which would increase the pool of free LysRS. Additionally, S207D LysRS has been shown to trigger a more "open" conformation, resulting in abolition of aminoacylation but not tRNA binding capacity in vitro (16,43). Our data are consistent with these previous findings and also show that S207D LysRS still binds tRNA Lys3 as well as WT LysRS.…”
Section: Discussionsupporting
confidence: 82%
“…19a–c). The model of the KRS T52D mutant suggested that phosphorylation at T52 could open up the ABD-CD interface and disturb the binding pocket for AIMP2, the binding partner of KRS within MSC 14,24 , thereby releasing p-T52 KRS from MSC (Fig. 4a and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A fusion protein of human AIMP2 1–48 with TRX (thioredoxin) was constructed as described previously 24 . The purified protein was then labeled with EZ-Link-NHS-PEG 12 -Biotin according to the vendor’s instructions (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…An intriguing observation that highlights the dynamic nature of LysRS within the cell, is illustrated by its mobilization to the nucleus (37). In the MSC, LysRS interacts with the dimeric p38 protein in a unique ␣ 2 ␤ 1 :␤ 1 ␣ 2 geometry; which is designed to control both retention and mobilization of LysRS from the MSC (16). In response to an immunological challenge, specific phosphorylation of Ser-207 of hLysRS has been shown to result in release of LysRS from the MSC and enhanced diadenosine tetraphosphate synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…LysRS is also part of the high molecular weight multisynthetase complex (MSC) present in higher eukaryotes (15). Within the MSC, LysRS specifically interacts with the scaffold protein p38/ AIMP2 and is present in a unique ␣ 2 ␤ 1 :␤ 1 ␣ 2 orientation, which is designed to control both retention and mobilization of LysRS from the MSC (16).…”
mentioning
confidence: 99%